Impact of Land Use Change on the Local Climate over the Tibetan Plateau - Jiming Jin; Shihua Lu; Suosuo Li; Norman L. Miller (Advances in Meteorology)
Observational data show that the remotely sensed leaf area index (LAI) has a significant downward trend over the east Tibetan Plateau (TP), while a warming trend is found in the same area. Further analysis indicates that this warming trend mainly results from the nighttime warming. The Single-Column Atmosphere Model (SCAM) version 3.1 developed by the National Center for Atmospheric Research is used to investigate the role of land use change in the TP local climate system and isolate the contribution of land use change to the warming. Two sets of SCAM simulations were performed at the Xinghai station that is located near the center of the TP Sanjiang (three rivers) Nature Reserve where the downward LAI trend is largest. These simulations were forced with the high and low LAIs. The modeling results indicate that, when the LAI changes from high to low, the daytime temperature has a slight decrease, while the nighttime temperature increases significantly, which is consistent with the observations. The modeling results further show that the lower surface roughness length plays a significant role in affecting the nighttime temperature increase.